RELASI GENDER SACHIKO MURATA (ANALISIS FILSAFAT TAO DAN SPIRITUALITAS ISLAM) - Fatrawati Kumari (Jurnal Ilmiah Ilmu Ushuluddin, 2013)
Thought -oriented feminism Indonesia with a Western perspective characteristic rational, materialistic and quantitative had been implicated in the occurrence of friction with the values in the eastern -oriented society that upholds harmonitas the characteristics, the spirituality, and the quality. Murata thought was based on Eastern perspective needed to be studied and received great attention, not only as an answer to the problems faced by the dominance of western orientation, but also as a counterweight to the tendency that the biassed too. Murata thought used the mystic Taoism and Islam, seeing the gender relations as relations dualist - complementary, relations two seemingly contradictory qualities, but it was one unit. The relationships found in all reality, include: people, nature and the God. Opposition of masculinity and femininity was not in the sense of separateness, but rather in the sense of unity, equality and reciprocity.